行星滚柱丝杠副的新发展及关键技术 - 刘更; 马尚君; 佟瑞庭; 关栋 (Jixie chuandong)
The planetary roller screw（PRS） is a mechanical transmission device that converting rotary motion into linear motion or vice versa,and it now has become the domestic and foreign research focus because of its characteristics of high-thrust,high-precision,high frequency response,and long life with the future development of all-electric aircraft and all-electric weapon,besides,the petroleum,chemistry industry and machine tool are also requirement.The basic working principle of PRS,the characteristics of five kinds of existing structure,application area and the most probable failure modes of PRS are introduced,and the research status and developmental trend of PRS from the aspects of the structure design,mechanics analysis and production manufacture are also summarized.Based on the summaries and related analysis,some suggestions are presented for future PRS research and development.